A STUDY ON DETERMINANTS OF ADOPTION OF OPEN DEFECATION FREE INNOVATIONS IN THALLI BLOCK OF KRISHNAGIRI DISTRICT - Roy, Sugata; Kalpana, B. (International Journal of Psychosocial Rehabilitation, 2020)
Open defecation is largely practiced for generations and it is highly accepted traditional practice and deeply rooted in minds of population in India. Free from open defecation is not a substance of access to toilets, but it is subjected to motivational factors and mind set of people. Economic condition, values, awareness and environment are determinants of adoption of open defecation free innovations among respondents. Significant difference is prevailing in determinants of adoption of open defecation free innovations among demographics of respondents. Economic condition, awareness, environment and values are positively and significantly impacting rate of success of open defecation free innovations among respondents. Therefore, adequate credit support and incentives should be given to respondents for construction of toilets and religious, social and communal groups must educate respondents to remove their cultural fear in the use of toilets.